The Impact of Corporate Social Responsibility on the Financial Performance in Nepalese Commercial Banks - Rai, Lok Bahadur (Pravaha, 2020)
The main purpose of this study is to examine the impact of Corporate Social Responsibility (CSR) on Return of Assets (ROA), Return of Equity (ROE) and Earnings per Shares (EPS) of commercial banks in Nepal. This study will be of immense use to the government, financial institutions and to other stakeholders. The data is obtained from the annual reports issued by the sample banks, and the study has covered the period of 2010-2018. The impact of ROE, ROE and EPS was tested on CSR. Similarly, to verify relationship between ROA, ROE, EPS and CSR the simple regression model was used. The regression model shows that ROA of Nepal Investment Bank and Standard Chartered Bank Nepal have no significant relationship with corporate social responsibility. ROE of Nepal Investment Bank has a significant relationship but Standard Chartered Bank Nepal has no significant relationship with CSR. Similarly, EPS of Nepal Investment Bank has a significant relationship but Standard Chartered Bank Nepal has no significant relationship with CSR. The study recommends that the financial institutions i.e. commercial banks should follow the directives given by the Central Bank (Nepal Rastra Bank) in the Monetary Policy for the F/Y 2016/17, in which Banks and Financial Institutions (BFIs) are asked to spend at least one percent of their profits in CSR activities and also CSR should be seen as an investment reported as such in financial statements of the financial institutions.